Revision of the leafhopper genus Gurawa (Cicadellidae: Deltocephalinae: Chiasmini) from Pakistan with description of a new species - Naveed, Hassan; Zhang, Yalin (Zootaxa, 2018)
The leafhopper genus Gurawa Distant, 1908 is revised with descriptions and illustrations of a new species, Gurawa longispina sp. nov. and a short winged form of Gurawa minorcephala Pruthi from Pakistan. A key is provided to distinguish known species in this genus from Pakistan.